Effect of three animal models of inflammation on nerve fibres in the synovium. - Mapp, P I (1994)
OBJECTIVES--Both sensory and sympathetic nerve fibres are depleted in the synovium in rheumatoid arthritis (RA). The hypothesis that the induction of an inflammatory response in the synovium is capable of causing depletion of nerve fibres was tested. METHODS--To investigate this phenomenon experimental arthritis in the rat was induced by three different methods and the synovium was examined for evidence of nerve depletion by immunocytochemistry. RESULTS--In a synovitis induced by latex spheres, a mainly macrophage foreign body type reaction, no nerve depletion was seen. In contrast both in an antigen-induced and a hydrogen peroxide-induced model of arthritis nerve fibre depletion was observed. This appeared to affect sensory and sympathetic nerve fibres equally. Nerve fibre depletion was only seen in areas of inflammatory cell infiltration indicating that a mixed lymphocyte and macrophage population of cells may be necessary for this effect. CONCLUSIONS--An inflammatory response, containing lymphocytes and macrophages, in the synovium is capable of the depletion of the finely myelinated and unmyelinated neuropeptide-containing nerves.